Analysis of plant pararetrovirus promoter sequence(s) for developing a useful synthetic promoter with enhanced activity in rice, pearl millet, and tobacco plants - Kumari, Khushbu; Sherpa, Tsheten; Dey, Nrisingha (Frontiers in Plant Science, 2024)
Promoter is one of the most important components for many gene-based research as it can fine-tune precise gene expression. Many unique plant promoters have been characterized, but strong promoters with dual expression in both monocot and dicot systems are still lacking. In this study, we attempted to make such a promoter by combining specific domains from monocot-infecting pararetroviral-based promoters Sugarcane Bacilliform Virus (SCBV) and Banana Streak Virus (BSV) to a strong dicotinfecting pararetroviral-based promoter Mirabilis Mosaic Virus (MMV). The generated chimeric promoters, MS, SM, MB, and BM, were tested in monocot and dicot systems and further validated in transgenic tobacco plants. We found that the developed chimeric promoters were species-specific (monocot or dicot), which depended on their respective core promoter (CP) region. Furthermore, with this knowledge, deletion-hybrid promoters were developed and evaluated, which led to the development of a unique dual-expressing promoter, MSD3, with high gene expression efficiency (GUS and GFP reporter genes) in rice, pearl millet, and tobacco plants. We conclude that the MSD3 promoter can be an important genetic tool and will be valuable in plant biology research and application.